Comparing compressed 2-dose and 3-dose melarsomine protocols in the era of adjunctive therapy: a randomized clinical trial of 168 dogs with heartworm disease - Linda S. Jacobson; Jessie L. Dyer; Adrienne Van Vlake; Brian A. DiGangi; Mirah A. Horowitz; Julie K. Levy (Journal of the American Veterinary Medical Association, 2026)
Abstract Objective To test the hypothesis that, when used with doxycycline, moxidectin, and prednisone, 2-dose melarsomine would be as safe and effective as 3-dose melarsomine. Methods A randomized clinical trial was conducted from April 2024 to December 2025, comparing compressed 2-dose and 3-dose melarsomine protocols. Dogs with Class 1 or 2 heartworm disease received sustained-release moxidectin, doxycycline, prednisone, and 2 or 3 injections of melarsomine. Melarsomine was administered on days 14 and 15 (2-dose group) or days 14, 44, and 45 (3-dose group). Dogs were exercise restricted for 4 weeks following melarsomine. Daily clinical observations were made until the last day of exercise restriction. Antigen tests were performed 6 or 9 months after melarsomine. Results 168 dogs completed treatment (2-dose group, n = 85; 3-dose group, 83), and 165 were retested (2-dose group, 85; 3-dose group, 80). There was no significant difference in efficacy between the 2-dose group (95.3%; 95% CI, 88.4% to 98.7%) and the 3-dose group (98.8%; exact 95% CI, 93.2% to 100.0%). The sample size was insufficient for conclusive noninferiority analysis at the predefined noninferiority margin of 4%. Survival was 100%. Complications were rare, with 7 dogs requiring thoracic radiographs with or without additional treatment, but none requiring intensive management. Incidence of post-melarsomine cough, increased respiratory effort, and weakness was not significantly different between groups. Conclusions A compressed 2-dose melarsomine protocol, with doxycycline, moxidectin, and prednisone, was safe and effective. Clinical Relevance Compared with 3-dose protocols, the 2-dose melarsomine protocol reduces the cost, resources, and time required to treat heartworm disease.